Creation of alternative energy by bio-ethanol production from pineapple waste and the usage of its properties for engine - Hossain, A.B.M.S.; Fazliny, A.R. (2010)
The world is facing problems of fossil fuels depletion. The problem of using fossil fuels can have an environmental impact due to the oxidation of CO(2), SO(2) and NO(X) emission. In order to overcome those problems, there is an alternative fuel that can replace fossil fuel such as bioethanol and biodiesel. Bioethanol can be derived from biomass with many different varieties of feedstocks such as corn, sugarcane, wood and fruits wastes that are renewable and sustainable resources, which are easily accessible and reliable and can help to clean the environment from the wastes. The experiment was conducted to prove that, bioethanol can be produced from rotten pineapples waste through the biochemical reaction called fermentation by commercial yeast, Saccharomyces cerevisiae which is suitable for running petrol engine. The influencing parameters that affect the production of bioethanol from pineapples wastes were optimized. The effects of pH, temperatures, fermentation period, substrate concentration with and without water, components of pineapples from rotten and fresh ones were investigated. From the results, the optimal yield of bioethanol in the parameters such as pH, temperatures, fermentation period, substrate concentrations was found to be 8.7% having pH 4 at 30 degrees C using 3 g/l. The result for viscosity was found under American Society for Testing Materials ( ASTM) standard in different concentration of yeast. The anhydrous ethanol was analyzed and it was found that, there was no dangerous element in it's acceptability as a transportation fuel based on ASTM standard. The elements that were mostly contained in the samples of ethanol production from pineapples wastes were Fe, Cu, Sn, Mn, Ag, Mo, Zn, P, Ca, Mg, Si, Na, B and V, but there was no significant difference among all elements.